2022
DOI: 10.1111/njb.03510
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition and phytogeographical spectrum of Pistacia vera L. woodland remnants in northeastern Iran

Abstract: The xerophilic woodlands of wild pistachio Pistacia vera L. remnants occur as several isolated stands in Central Asia. The Kopet Dagh mountain range, northeastern Iran, is the westernmost distribution range of wild pistachio. In this research, we present the annotated checklist of vascular plants of two remnants of P. vera woodlands along the Iran–Turkmenistan borders. We provide the life‐forms, phytogeographical spectrum, endemism and conservation status of the flora. The field surveys were conducted through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…B. tectorum , V. persica , and Z. fabago were the indicator species of D1011. These species are typical of plants that grow in disturbed areas of the Khorassan Province, Iran (Atashgahi et al, 2018, 2022; Erfanian et al, 2019). Our findings showed that indicator species can reflect the state of VLs.…”
Section: Discussionmentioning
confidence: 99%
“…B. tectorum , V. persica , and Z. fabago were the indicator species of D1011. These species are typical of plants that grow in disturbed areas of the Khorassan Province, Iran (Atashgahi et al, 2018, 2022; Erfanian et al, 2019). Our findings showed that indicator species can reflect the state of VLs.…”
Section: Discussionmentioning
confidence: 99%
“…These are isolated and remnant xerophilous stands of the wild pistachio as subtropical semi-savanna, occurring between altitudes 800 and 1,200 m a.s.l. from the western to eastern Kopet-Dagh Mts (Atashgahi et al 2022). Due to the low precipitation and high maximum temperature, the understory layer is mainly covered by winter and early-spring ephemeroids, including grasses such as Poa bulbosa and the sedge Carex pachystylis (Memariani et al 2016).…”
Section: Proposed Syntaxonomic Scheme Of Pistachio Open Woodlandsmentioning
confidence: 99%
“…It mainly includes the colline and montane belt of Eastern Hindu Kush, western Pamir-Alai, western Tian Shan and Kopet-Dagh. The Kopet-Dagh mountain range, northeastern Iran, is the westernmost distribution range of wild pistachio (Atashgahi et al 2022). It grows between 400 and 2,000 m a.s.l.…”
Section: Pistacietalia Veraementioning
confidence: 99%
“…These are isolated and remnant xerophilous stands of the wild pistachio as subtropical semi-savanna, occurring between altitudes 800 and 1,200 m a.s.l. from the western to eastern Kopet-Dagh Mts (Atashgahi et al 2022). Due to the low precipitation and high maximum temperature, the understory layer is mainly covered by winter and early-spring ephemeroids, including grasses such as Poa bulbosa and the sedge Carex pachystylis (Memariani et al 2016).…”
Section: Proposed Syntaxonomic Scheme Of Pistachio Open Woodlandsmentioning
confidence: 99%
“…It mainly includes the colline and montane belt of Eastern Hindu Kush, western Pamir-Alai, western Tian Shan and Kopet-Dagh. The Kopet-Dagh mountain range, northeastern Iran, is the westernmost distribution range of wild pistachio (Atashgahi et al 2022). It grows between 400 and 2,000 m a.s.l.…”
Section: Pistacietalia Veraementioning
confidence: 99%